Morphological Mapping of Seabed for Monitoring Sedimentation at Ulee Lheu Fishing Jetty Using Single Beam Dual Frequency - Guntur Adhi Rahmawan; Koko Ondara; Ilham Adnan (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2021)
ABSTRACTUlee Lheu Fishing Port Jetty is an important port in Banda Aceh City which functions as a crossing, loading and unloading port. The issue of sedimentation is the main problem. This study aims to determine the morphology of the seabed as the basis for monitoring sedimentation at the Ulee Lheu Fishing Port Jetty. Bathymetric surveys were carried out in the dock pool using a single beam echotrack odometer. Tides were obtained using the IOC Sea Level Monitoring for 29 days and analyzed using the admiralty method. The results of the processing showed that there was sedimentation in the area of the Ulee Lheu Fishing Port Jetty. The depth of the wharf pool ranges from 0-7,7 meters with a sediment volume of 250.117,15 m3. Meanwhile, the tidal water type is included in the double daily tidal type with a value of F = 0,15 and the tidal distance is 2,38 meters and is included in the micro tidal range category and there is sedimentation in the Ulee Lheu Fishing Port Jetty.Keywords: Bathymetry, sedimentation, morphology, Ulee Lheu Port, tidal rangeABSTRAKDermaga Perikanan Ulee Lheu merupakan pelabuhan penting di Kota Banda Aceh yang difungsikan sebagai pelabuhan penyeberangan maupun sebagai pelabuhan bongkar muat. Isu sedimentasi menjadi masalah utama di dermaga ini. Penelitian ini bertujuan untuk mengetahui morfologi dasar laut sebagai dasar pemantauan sedimentasi di Dermaga Perikanan Ulee Lheu. Survei batimetri dilakukan di kolam dermaga menggunakan echotrack odometer single beam. Pasang surut diperoleh menggunakan dari IOC Sea Level Monitoring selama 29 hari serta dianalisa menggunakan metode admiralty. Hasil pengolahan menunjukan terjadi sedimentasi di areal Dermaga Perikanan. Kedalaman kolam dermaga berkisar antara 0-7,7 meter dengan volume sedimen berkisar 250.117,15 m3. Sementara tipe pasang surut perairan termasuk dalam tipe pasang surut harian ganda dengan nilai F=0,15 serta jarak tunggang pasut sebesar 2,38 meter dan termasuk dalam kategori mikro tidal range dan terdapat sedimentasi di bagian Dermaga Perikanan Ulee Lheu.Kata Kunci : Batimetri, Sedimentasi, Morfologi, Dermaga Perikanan Ulee Lheu, tunggang pasang surut